METODE EVALUASI SATU-SATU BAHAN AJAR MATA KULIAH STATISTIKA MATEMATIKA BERBASIS PEMECAHAN MASALAH SERTA BERNUANSA ISLAMI - Fitri, Wanda; Utami, Nita Putri (Math Educa Journal, 2020)
Creating an academic culture that is conducive to intellectual development, the character of the academic community and mathematics education staff is one of the missions of the Tadris Mathematics study program at UIN IB Padang. Therefore, the conditions of the lecture greatly determine the implementation of the mission of the Mathematics Tadris study program. To create optimal lecture conditions, it can be supported by the presence of teaching materials in lectures. Teaching materials that facilitate students in such a way as to create an attractive lecture atmosphere is one of the responsibilities of a lecturer. However, the reality is that in the field, the attractiveness of students in lectures is still low due to the unavailability of optimal teaching materials. Mathematics statistics is one of the most important subjects, meaning that it is very widely used when they have become teachers and assist in the making of final assignments. By providing teaching materials for this course which contains Islamic nuances, it aims to provide the characteristics of prospective teachers who graduate from UIN IB Padang. So the formulation of the problem in this research is how the process and results of the development of teaching materials for mathematics statistics courses based on practical problem solving and Islamic nuances in one-on-one evaluations.